New report of Mesostenus transfuga Gravenhorst, 1829 (Ichneumoni-dae - Hymenoptera) from Karbala Province in Iraq - Aljaafari, Raad K. (Journal of Kerbala for Agricultural Sciences, 2022)
Mesostenus transfuga Grav., 1829 is recorded first time in Karbala city about 100km south of Baghdad. The specimens assessed were from Karbala city. This parasitoid wasp is very imported as a bioagent against key pests. It is important to understand the diversity of beneficial insects in the area of study and how to keep them up